Supplementary Table S3 from The EstroGene Database Reveals Diverse Temporal, Context-Dependent, and Bidirectional Estrogen Receptor Regulomes in Breast Cancer - Zheqi Li (14961021) (2025)
Metadata of four RNA-seq experiments for inter-data set concordance analysis